TEACHING BASIC VOCABULARY AND PHRASES - Anorboyeva Mahbuba; Ahmadjonova Gulhayo (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Vocabulary is understanding how to use words in relation to their meaning. Developing new vocabulary involves more than just looking up words in a dictionary and using those words in sentences. Students’ vocabulary grows throughout their lifetime through direct and indirect learning.